Huntingtin-Associated Protein 1 in Mouse Hypothalamus Stabilizes Glucocorticoid Receptor in Stress Response - Chen, Xingxing; Xin, Ning; Pan, Yongcheng; Zhu, Louyin; Yin, Peng; Liu, Qiong; Yang, Weili; Xu, Xingshun; Li, Shihua; Li, Xiao-Jiang (Frontiers in Cellular Neuroscience, 2020)
Huntingtin-associated protein 1 was initially identified as a brain-enriched protein that binds to the Huntington’s disease protein, huntingtin. Unlike huntingtin that is ubiquitously expressed in the brain, Hap1 is enriched in the brain with the highest expression level in the hypothalamus. The selective enrichment of Hap1 in the hypothalamus suggests that Hap1 may play a specific role in hypothalamic function that can regulate metabolism and stress response. Here we report that Hap1 is co-localized and interacts with the glucocorticoid receptor (GR) in mouse hypothalamic neurons. Genetic depletion of Hap1 reduced the expression level of GR in the hypothalamus. Dexamethasone, a GR agonist, treatment or fasting of mice induced stress, resulting in increased expression of Hap1 in the hypothalamus. However, when Hap1 was absent, these treatments promoted GR reduction in the hypothalamus. In cultured cells, loss of Hap1 shortened the half-life of GR. These findings suggest that Hap1 stabilizes GR in the cytoplasm and that Hap1 dysfunction or deficiency may alter animal’s stress response.